KORELASI REWARD DAN PUNISHMENT TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 1 SALIMPAUNG KABUPATEN TANAH DATAR - Yayan Rahadian (al-fikrah: Jurnal Manajemen Pendidikan, 2018)
The problem in this research was students motivation in Islamic education in high school 1 Salimpaung is well. Researcher suppose that this condition process. The purpose of this research was to know the correlation of reward toward student motivation, punishment toward students motivation and the correlation both of reward and punishment toward students motivation. This research is quantitative research that applied correlation method. The population in this research were all of the students in high school 1 Salimpaung in 2016/2017. It was consists of 417 students. While, the sample was only 81 students that was taken by using proportional stratified random sampling technique. The variable data X1, X2, and Y collected by using questioner with liker scale. The first and second hypothesis tested by using simple regression technique. While the third hypothesis tested by using double regression. The result of this research indicate that the correlation of reward toward students motivation was 0,1%, then correlation of punishment toward students motivation was 10,3%. While the correlation both reward and punishment toward students motivation was 10,4%.